Analysing the Role of Religious Education: Changes in Personality Wellbeing among People Affected by Flood Disaster - Yaakub, Muhamadul Bakir; Othman, Khatijah; Nik Nazli, Nik Nadian Nisa (2018)
This study focus on the role of religious education and changes in personal well-being in responding to the flood disaster. It investigates the relationship of trauma events towards perceived knowledge, religious personality, and well-being. Structural Equation Modelling-Partial Least Squares methodology was used to assess the hypothesized model that linked all the constructs of traumatic events and perceived knowledge with the religious personality and well-being. This research employed a comprehensive instrument that defines various factors influencing the flood victim behaviors such as the state of religious understanding, together with its varied aspects of beliefs systems, structure, the practices of religious principles and values that shape an individual personality.The questionnaires were distributed to 348 flood victims at Kelantan and Pahang. From the analysis, it reveals that all the relationships in the hypothesized model were significant and this shows that all constructs of trauma events, perceived knowledge, religious personality and well-being play a vital role within religious education indicators.